The scope of Brazilian Research on Pedagogical Practices and Teaching Practices: theoretical considerations and positions - Giraldi, Luciana Ponce Bellido; Perez, Marcia Cristina A. (Faculdade de Filosofia e Ciências, 2019)
The aim of this text was to identify and analyse Brazilian productions dedicated to studying teaching and pedagogical practices. For this, bibliographic reviews were organized in the following databases: CAPES/MEC, Scielo and Ibict. We analyzed 28 studies, selected according to previously established criteria. Se analizaron 28 trabajos, seleccionados según criterios previamente establecidos. It was possible to conclude that researches on pedagogical practices covered a varied number of themes, which makes it difficult for the collective constitution of knowledge resulting from such studies. In addition, localized investigations refer, a priori, to the need for changes and or innovations in teaching practices, often without even understanding what has been done concretely in classrooms. Finally, it was pointed out that no research was found that related student actions and teaching practices in concrete school contexts. Recebido em: 18/02/2018.Aprovado em: 13/06/2019.